Position of the Financial Services Authority in Bankruptcy of Securities Companies - Syahrul, Syahrul; Mujahid, Mujahid; Suyuthi, Nurmadhani Fitri (Journal La Bisecoman, 2023)
Human resource management of a company is an important component. The process of managing human resources itself is an effort to obtain reliable workers who can do their jobs properly and responsibly. A leader of a government organization can apply several behaviors, including adopting the right leadership style, to realize good employee task activities. The purpose of this study was to analyze the transformational leadership style in Perumda Air Minum Danum Taka, Penajam Paser Utara Regency. This study uses a qualitative approach with in-depth interviews with key informants from the Central Financial Services Authority. Based on the results of the study in the discussion, it was found that the position of the financial services authority in a bankruptcy petition is a requirement so that a bankruptcy petition against a securities company can be submitted, and Transformational leadership style plays a very important role in creating positive change, motivating team members and achieving better results. The author suggests that the Financial Services Authority as a supervisory institution and as an institution that has a position in submitting a bankruptcy statement application should provide more comprehensive supervision to be able to guarantee the rights of the Indonesian people in entrusting their finances to securities companies that manage large finances and based on POJK Number 6/POJK.04/2021 should implement risk management to avoid bankruptcy.